(untitled) (Journal of Oriental Studies, 2025)
In recent years, the «Look to the East» has emerged as a key strategic direction in the foreign policy of the Islamic Republic of Iran. This orientation began to take shape in the 1990s and has gradually intensified in response to growing Western pressure. This article aims to examine the stages and main dimensions of Iran’s «Look to the East» strategy. Employing comparative-historical and chronological methods, the study investigates the causes of this policy shift, the mechanisms and phases of its implementation, as well as its outcomes. Drawing on the findings of Iranian, Russian, and Western scholars, the article argues that the evolution of this strategy has been significantly influenced by the changing global geopolitical landscape and the increasing pressure exerted by the West over Iran’s nuclear program. The analysis focuses on Iran’s relations with Russia, China, and India — particularly in terms of shared political and economic interests — as core elements of the «Look to the East» strategy. In addition, Iran’s efforts to engage with international organizations are considered as part of this broader policy trajectory. Ultimately, the deepening of ties with Eastern countries is seen as a means to safeguard Iran’s geopolitical and economic interests. Understanding the rationale and components of the «Look to the East» provides valuable insight into Iran’s foreign policy and its evolving role in international affairs. Keywords: Iran, foreign policy, look to the East, Russia, China, India, international organizations.